Plan de marketing para la comercialización del té de horchata bebida aromática saludable de industria ILE en el cantón Quevedo año 2015 - Estrada Zambrano, Eduardo Raúl (2016)
This research work is based on a marketing plan to increase market share and increase sales volume in the company Ile dedicated to the commercialization of Spiceries, seasonings and aromatic , with the aim of improving the marketing of tea horchata in the canton Quevedo, incorrect aplication of marketing strategies hurts the company , the decrease in sales volume because it does not have a plan advertising in mass media for proper marketing, They have not allowed them to increase market share, and therefore, positioning is low causing low profitability. To carry out this research various techniques and research methods, which provided us with the primary data collection were executed which they were obtained from surveys held the economically active population of the canton Quevedo on tea consumption, identifying unmet demand and ignorance in the market over tea horchata in the situational analysis of the company , although there are several brands and flavors of tea in the market there is a high rate of customers who are willing to consume tea horchata, well within the investigation it was found that there is a lack of product benefits, because they lack advertising to be known in the market and achieve possession in the minds of consumers strategies. With the results of research designed marketing strategies training the sales force in media advertising and promotions including free samples , tastings , flyers, billboards ; so that consumers know and lean for the product and thereby increase the volume and market share .